Mechanism for the digital transformation of an enterprise’s logistics system - Kovalska, Liubov; Topalov, Roman (Global Prosperity, 2025)
Abstract. The article develops a mechanism for the digital transformation of an enterprise’s logistics system. The mechanism of digital transformation of an enterprise’s logistics system is proposed to be understood as a set of elements (blocks) that are individualized depending on the levels of digital maturity of the enterprise’s logistics system, the implementation of which, under the influence of environmental factors, makes it possible to form its SMART logistics system. Four structural blocks of the mechanism of digital transformations of an enterprise’s logistics system are identified: Block 1 – diagnostic and target-oriented (diagnostics of the digital transformation of the enterprise’s logistics system, determination of the mission and goals of digital transformation); Block 2 – managerial (identification of the subject, object, strategy, and vectors of digital transformation of the enterprise’s logistics system); Block 3 – executive (tools for the digital transformation of the enterprise’s logistics system); Block 4 – result-oriented (assessment of the results of strategy implementation, identification of the level of goal achievement, elimination of deviations). A matrix of the SMART logistics system of the enterprise has been constructed. A differentiated approach to selecting the goals of digital transformation of the enterprise’s logistics system has been substantiated. The vectors of digital transformation of the enterprise’s logistics system have been identified: creation of digital supply chains; development of digital business; formation of design thinking; implementation of digital future; development of logistics 5.0. The tools for the digital transformation of the enterprise’s logistics system have been substantiated: development of digital literacy of management and logistics personnel of the enterprise; creation of a green supply chain; development of the enterprise’s digital logistics infrastructure.